Efficacy of L-carnosine against Schistosoma mansoni antigens in liver, heart, kidney and brain of rabbits - Naima Z. Mohamed, Monira A.Abd El Kader, Sanaa A. Ali (Journal of Applied Pharmaceutical Science, 2013)
The present investigation was an attempt to study the enhancememt effect of L-carnosine (beta alanyl-l-histidine) on the influence of vaccination on healthy (non-infected) rabbits treated with Schistosoma mansoni egg antigens, cercariae antigens, and worms antigens as protective agents against infection. This study involved individual injection of three Schistosoma mansoni antigens: soluble egg antigen (SEA), cercarial antigen preparation (CAP) and soluble worm antigen preparation (SWAP), in three rabbit groups, respectively. Three other groups each received the same specific antigen in conjunction with the administration of L-carnosine, biochemical parameters including DNA, RNA, DNA/RNA ratio concentrations in addition ATPase, and acetyl cholinesterase activities were measured in liver, heart, kidney and brain in all groups. Elevation in most parameters was observed in the immunized groups. Carnosine treatment of rabbit groups immunized with SEA, CAP and SWAP in comparison to the non-carnosine-treated immunized groups resulted in amelioration the changes of DNA, RNA, ATPase and acetyl cholinesterase activities in most groups. L-carnosine has a beneficial effect in the amelioration of the changes in biochemical parameters as a result of S. mansoni antigen immunization.
Keywords: Antigens, DNA, RNA, DNA/RNA, ATP ase, Acetyl cholinesterase.